Теоретичні і методичні засади підготовки майбутніх учителів іноземних мов в університетах США - Леврінц Маріанна; Lőrincz Marianna; Levrints Marianna (My University, 2020)
Резюме. У дисертації здійснено системний аналіз професійної підготовки вчителів ІМ в університетах США, схарактеризовано теоретичні, дидактичні й організаційні особливості функціонування іншомовної педагогічної освіти у США, обґрунтовано можливості використання прогресивного досвіду досліджуваної країни у вітчизняній практиці підготовки вчителів ІМ. У дослідженні проаналізовано сутність професійної підготовки вчителів ІМ у США, виявлено ключові методологічні положення, що зумовлюють тенденції розвитку і функціонування системи підготовки вчителів ІМ у США, особливості формування фахової компетентності майбутніх учителів ІМ, організаційні умови і дидактичні підходи у підготовці вчителів галузі іншомовної освіти у США. Виявлено подібні й відмінні риси систем підготовки вчителів ІМ в університетах України і США, на основі чого запропоновано шляхи поліпшення вітчизняної галузі іншомовної педагогічної освіти з урахуванням інноваційних ідей досвіду США. Розроблено авторську класифікацію моделей підготовки вчителів ІМ. Розглянуто підходи до формування фахової компетентності майбутніх учителів ІМ в університетах США. Окреслено дидактичні підходи до формування іншомовної комунікативної, методичної, культурологічної та науково-дослідницької компетентностей майбутніх учителів ІМ у педагогічній теорії і практиці США. Схарактеризовано сучасний стан іншомовної освіти США. Здійснено докладне вивчення підходів до формування методичної компетентності вчителів ІМ на основі 25 силабусів курсів методики викладання ІМ. Представлено систему професійної підготовки вчителів ІМ в університетах США, схарактеризовано її структуру, інтеграційні властивості, елементи, принципи, ознаки, законодавчу базу, концептуальну спрямованість. Обґрунтовано, що підготовка вчителів ІМ є підсистемою національної системи вищої освіти США, демонструючи властивості відкритості, динамічності, цілеспрямованості й гнучкості, які сприяють її когерентності і діалектичній взаємозв’язаності; схарактеризовано методологічні підвалини, які зумовили ґенезу і сучасний стан системи підготовки вчителів ІМ, концептуальні положення, на які спирається функціонування й удосконалення означеної системи; проаналізовано організаційно-змістові і дидактичні умови професійної освіти вчителів ІМ; виявлено сучасні тенденції функціонування системи іншомовної педагогічної освіти у США. Розглянуто організаційно-змістові підходи підготовки вчителів ІМ у США на основі навчально-методичної документації 45-и освітніх програм. Представлено якісно-кількісні характеристики освітніх програм. Проаналізовано особливості практичної підготовки та організацію науково-дослідницької діяльності майбутніх учителів ІМ в університетах США. Схарактеризовано сучасні тенденції розвитку іншомовної педагогічної освіти в Україні. Представлено результати компаративного аналізу систем підготовки вчителів ІМ в Україні і в США. Отримані порівняльні дані тенденцій розвитку й функціонування освітніх систем вищезгаданих країн дали змогу виділити перспективні напрями модернізації вітчизняної галузі підготовки вчителів ІМ з урахуванням інноваційних ідей досвіду США на державному, інституційному та особистісному рівнях за нормативно-правовим, концептуальним й організаційно-змістовим напрямами.

Abstract. In the thesis a systematic analysis of foreign language teacher education in the US universities has been carried out, its theoretical, didactic and organizational underpinnings have been highlighted with a view of identifying possibilities of utilizing flagship ideas of the US teacher preparation experience to advance the system of language teacher education in Ukraine. The thesis is a comprehensive examination of the key tenets of the field of foreign language teacher education and its basic methodological framework which determine the ontology, developmental trends and functioning of the language teacher education system in the US universities, student teachers’ competence development, organisational and didactic approaches salient in language teacher education in the USA. Furthermore, congruencies and discrepancies in the mainstream practices of language teacher preparation in the Ukrainian and American universities have been accentuated for the purpose of proposing venues of reforming the national teacher education system of Ukraine based on the innovative ideas drawn from the US experience. The US language teacher education system is shaped under the influence of ethnolingual pluralism, unstable reality which pushes it towards proliferation of the methodological-philosophic stance, dynamic worldview and epistemological polyvariance, focus on the sociocultural context, and anthropocentrism. The relevant conceptual orientations impacting the sphere of language teacher education are the constructivism (construction of meanings under the influence and within the sociocultural environment), humanism (holistic personality formation), neopragmatism (self-actualisation), postmodernism (rejection of dogmatism in education) and critical pedagogy (social justice movement). The theoretical framework of the system of foreign language teacher education in the USA is a combination of symbiotic scientific approaches (culturological, interdisciplinary, anthropocentrical, ambivalent, acmeological, axiological, empirical) and educational principles (autonomy, connection between educational theory and practice, creating conditions conducive to self-actualisation, attending to individual needs, tolerance for and acceptance of individual differences and cultural diversity, humanisation, self-regulation, continuous learning, collaboration, pragmatism etc.). Based on a set of criteria several language teacher education models have been singled out. The quality of the US system of foreign language teacher education is assured by mandating the requirements in the standards of teacher preparation and development, implementation of external and internal accountability measures, licensing and certification of teachers, evaluation of teaching effectiveness, improvement of teacher education programmes, teacher induction etc. Approaches to the development of foreign language teaching competence have been scrutinized. Mainstream practices in the development of foreign language teaching competence in the US universities include increased control over the quality of teacher preparation programmes, assessment of student teachers’ oral proficiency, implementation of the external evaluation procedures, greater focus on the selection and practicality of the content of educational programmes by means of enriching the range of profession-related disciplines, increased integration of teaching practicum, earlier and extended field experience, collaboration between the subjects of the educational system and stakeholders etc. The study has expanded on the didactic approaches of the communicative, pedagogical content, cultural and research competences development of prospective foreign language teachers in the US universities. Approaches to the development of pedagogical content competence have been subjected to detailed analysis on the basis of twenty five syllabi of foreign language teaching methods course. The system of foreign language teacher education in the US universities has been presented, together with its structure, integrative characteristics, elements, principles, legislative basis, and conceptual orientation. The system-activity research approach made it possible to characterize the US system of foreign language teacher education as a holistic, systemic entity exhibiting the characteristics of openness to interaction and interconnection with other social systems, dynamism by evolving in line with social transformations, purposefulness by reflecting on societal demands, adaptability to sociocultural reality, and decentralization of management. The aforementioned system’s structure comprises internally discrete components (normative-legislative, organizational-procedural, target, curricular/content, diagnostic and conceptual). The uniqueness of the system-forming characteristics is determined by the extended efforts at modernization and reforming of the system at all educational levels, prioritizing the quality assurance of education as key to the country’s sustainable development, ensuring equal access and inclusion of all citizens to quality education, promoting intercultural and transethnic articulation, creating optimum conditions for individual self-realisation. The integrative properties of the system are diversity and inclusion, continuous learning, personalisation, individualisation, differentiation, standardisation, fundamentalisation, digitalisation, collaboration/partnership. Effective foreign language teacher education is sustained at several levels: educational policy level – embedded in the idea of quality assurance and professionalism of the teaching corpus, standartisation in teacher preparation and development; institutional level – expanding the range and types of educational programmes, knowledge-base/content of the foreign language teacher education field; governance level – autonomy of institutions of higher education, striking balance between spheres of federal and public influence, accreditation, certification and licensing by independent professional agencies; organisational level – revisiting approaches to the development of student teachers’ competence in light of holism and interdisciplinarity (integrated instruction of language and content area); individual level – the development of teacher’s personality, dispositions for teaching, commitment, motivation etc. The principles of content selection of the foreign language teacher education field have been explored on the basis of 45 curricula of the respective programmes in the US universities, in the result of which their quantitative and qualitative characteristics have been established. The practical component in the system of language teacher preparation relies on the principles of professional relevance, coherence between theory and practice, collaboration between the protagonists of the educational system, diversification of clinical experiences, of their organizational and didactic approaches, consistency and continuity, autonomy; its quantitative characteristics have been explored. In the thesis general tendencies in the development of foreign language teacher preparation in Ukraine have been disclosed. Findings of the comparative analysis of the systems of language teacher education in Ukraine and the USA are reported. Commonalities and discrepancies in the systems of teacher preparation of the two countries have been revealed. The comparative data served as a ground for propositions aimed at reforming the Ukrainian system of foreign language teacher preparation taking into account the positive elements of the US experience at the state, institutional and individual levels along the normative-legislative, conceptual and organizational strands.
Дисертація на здобуття наукового ступеня доктора педагогічних наук
Keywords: іншомовна педагогічна освіта; професійна підготовка вчителів іноземних мов; майбутній учитель; система; освітня програма; фахова компетентність; дидактичні підходи; університет; США